Neonate with congenital absence of the nose: case report - Nieto-Sanjuanero, Adriana; García-Ramírez, Arturo; Martínez-Cobos, María; Martínez-Garza, Edmundo; de la O-Cavazos, Manuel; Quintanilla-Loredo, Ramón; Rodríguez-Garza, Claudia; Méndez-Sáenz, Marco (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The congenital absence of the nose is called arrhinia and according to the Losee et al classification, it is type I. Total arrhinia is considered if it is associated with the absence of the olfactory system (olfactory tracts and bulbs). In Mexico, there is only one reported case of arrhinia. In this case report, we presented a neonate with a congenital absence of the nose. The absence of olfactory tracts and bulbs was verified with imaging and pathological studies, classifying it as total congenital arrhinia. This case was the first of its type in our country. Since it was a rare condition, there was little bibliography on its management, therefore, coordination between the different specialties is important for proper management.